Efficient and Scalable Culture of Single Dissociated Human Pluripotent Stem Cells Using Recombinant E8 Fragments of Human Laminin Isoforms. (2nd February 2015) - Miyazaki, Takamichi; Kawase, Eihachiro
Abstract: This unit describes a protocol for efficient expansion of human pluripotent stem cells (hPSCs). A key feature of this method is subculture of hPSCs by single‐cell dissociation passaging on substrates coated with recombinant E8 fragments of human laminin isoforms (LM‐E8s). LM‐E8s, provide superior adhesion over intact laminin isoforms and Matrigel. Single hPSCs seeded on LM‐E8s show accelerated migration and rapid reconstruction of clusters, resulting in robust survival and proliferation. This protocol yields 200‐fold more hPSCs than conventional subculture methods in 1 month of culture. Furthermore, this protocol can be easily adapted to most hPSC lines in combination with the use of various xeno‐free, defined culture media, and large‐scale expansion of hPSCs is easily achievable to facilitate the practical applications of hPSCs. © 2015 by John Wiley & Sons, Inc.